2013
DOI: 10.1016/j.funbio.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Species of Mycosphaerellaceae and Teratosphaeriaceae on native Myrtaceae in Uruguay: evidence of fungal host jumps

Abstract: Mycosphaerella species are well-known causal agents of leaf diseases on many economically and ecologically important plant species. In Uruguay, a relatively large number of Mycosphaerellaceae and Teratosphaeriaceae are found on Eucalyptus, but nothing is known of these fungi on native Myrtaceae. The aim of this study was to identify Mycosphaerellaceae and Teratosphaeriaceae species associated with leaf diseases on native Myrtaceae in Uruguay and to consider whether host jumps by the pathogen from introduced Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Analysis of the ‘core fungal diversity’, defined as taxa present in at least 25% of all samples, found that 114 of the genera were in at least 25% of the restroom floor samples (Tables S1 and S2). Thirty‐six families of fungi were found in all restroom samples, including the Mycosphaerellaceae, a diverse fungal family containing many known plant pathogens which composed ~10% of the sequence reads, and Teratosphaeriaceae, which are common Eucalyptus pathogens (Pérez et al., ). Eucalyptus trees originating from Australia have been planted by the millions in San Diego since the early 1800s (Stanford, ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the ‘core fungal diversity’, defined as taxa present in at least 25% of all samples, found that 114 of the genera were in at least 25% of the restroom floor samples (Tables S1 and S2). Thirty‐six families of fungi were found in all restroom samples, including the Mycosphaerellaceae, a diverse fungal family containing many known plant pathogens which composed ~10% of the sequence reads, and Teratosphaeriaceae, which are common Eucalyptus pathogens (Pérez et al., ). Eucalyptus trees originating from Australia have been planted by the millions in San Diego since the early 1800s (Stanford, ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 48 families found in the 1,524 fungal OTUs, no fungal families likely adapted specifically to the canopy in the forest (Fig 5). The phyllosphere fungi living in the canopy in the forest were composed of common fungi, many of which are known to be pathogens in plant leaves or woods [58, 59], saprobes and endophytes [60]. They have small conidia that enable them to spread over long distances [61] and thus are found in a wide range of ecological habitats in the temperate and tropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Although these genera are chiefly delineated based on their DNA sequence data, in most cases they also correlate with the distinct morphology of their asexual morphs (Crous et al 2009b). Much of the research on this complex in recent years has been based on revising the mycosphaerella-like fungi associated with specific plant hosts like Acacia (Crous et al 2004c), Eucalyptus (Crous et al 2004b, Cheewangkoon et al 2008, Citrus Braun 2003, Pretorius et al 2003), Musa , Proteaceae and Myrtaceae , Perez et al 2013. In the present study we aimed to determine which cercosporoid species occur on Citrus, focusing primarily on those isolated from various Citrus plantations in China.…”
Section: Discussionmentioning
confidence: 99%